Evaluación y Caracterización de la sustentabilidad en fincas productoras de cacao (Theobroma cacao L.) del Cantón Baba, provincia de Los Ríos - COLOMBATTI MORAN JAIME RENATO (2025)
In this work, the research on the Evaluation and Characterization of sustainability in cocoa producing farms in the Baba canton, Los Ríos province is presented. This research will be carried out in the cocoa producing farms in the city of Baba, also known as San Francisco de Baba, is an Ecuadorian city, belonging to the Province of Los Ríos. It is located in the center of the Ecuadorian coastal region, very close to the Arenal River. In the census that was carried out in 2022, it had a population of 6,746 inhabitants, making it the one hundred and twenty-fifth most populated city in the country, at the Coordinates 1°47'06″S 79°40'40″W. This agricultural area of the country is a producer of a great diversity of crops such as rice, corn, soybeans, cocoa, banana, plantain and a great diversity of fruit crops. This cocoa area is made up of 160 cocoa producers who coexist with the cultivation and It is a means of livelihood of great importance for farmers and with this research work, information of real importance will be collected to be able to identify various problems that they present and know about the characterization, varieties of the crop, phytosanitary management, sustainability indicators with respect to pests, diseases and the sustainability that farmers obtain from the crop. Once the study was carried out in this agricultural area, important results were obtained, such as that their main problem is with monilla and arriera insects, the main problem of low production, that their plantations are diversified, that they help themselves financially with animal husbandry, and they receive advice. technical and financial of the state, its farms are its own, it has a deficiency in crop nutrition, irrigation in the dry season, solve phytosanitary, nutritional and water problems, strengthen financing by private and state banks to invest in the crop and thus improve its production